Odpowiedź :
Zadanie 1
Liczymy wartość wyrażenia:
[tex]8:(8-1:(8-1:8))=8:\Big(8-1:\Big(8-\dfrac{1}{8}\Big)\Big)=\\\\\\=8:\Big(8-1:\Big(\dfrac{64}{8}-\dfrac{1}{8}\Big)\Big)=8:\Big(8-1:\dfrac{63}{8}\Big)=\\\\\\=8:\Big(8-\dfrac{8}{63}\Big)=8:\Big(\dfrac{504}{63}-\dfrac{8}{63}\Big)=\\\\\\=8:\dfrac{496}{63}=8\cdot\dfrac{63}{496}=\dfrac{63}{62}[/tex]
Liczymy 62% wartości tego wyrażenia:
[tex]0,62\cdot\dfrac{63}{62}=\dfrac{62}{100}\cdot\dfrac{63}{62}=\dfrac{63}{100}=\boxed{0,63}[/tex]
Zadanie 2
Liczymy wartość wyrażenia:
[tex]7:(7-1:(7-1:7))=7:\Big(7-1:\Big(7-\dfrac{1}{7}\Big)\Big)=\\\\\\=7:\Big(7-1:\Big(\dfrac{49}{7}-\dfrac{1}{7}\Big)\Big)=7:\Big(7-1:\dfrac{48}{7}\Big)=\\\\\\=7:\Big(7-\dfrac{7}{48}\Big)=7:\Big(\dfrac{336}{48}-\dfrac{7}{48}\Big)=\\\\\\=7:\dfrac{329}{48}=7\cdot\dfrac{48}{329}=\dfrac{48}{47}[/tex]
Liczymy 47% wartości tego wyrażenia:
[tex]0,47\cdot\dfrac{48}{47}=\dfrac{47}{100}\cdot\dfrac{48}{47}=\dfrac{48}{100}=\boxed{0,48}[/tex]